Groundwater compatibility with formation water and pay zone rocks in Pervomaysk oil-gas-condensate field to maintain formation pressure - Trifonov, Nikolay Sergeevich; Nazarov, Aleksandr Dmitrievich; Alekseev, S.V. (IOP Publishing, 2016)
The paper describes the research results in determining the compatibility of groundwater from Aptain-Albian-Cenomanian aquifer with formation water and pay zone rocks in U1 layer sediments, Pervomaysk oil field.
Keywords: подземные воды; Первомайское нефтяное месторождение; пластовое давление